The (lack of) distortionary effects of proxy-means tests: Results from a nationwide experiment in Indonesia - Abhijit V. Banerjee; Rema Hanna; Benjamin A. Olken; Sudarno Sumarto (Journal of Public Economics Plus, 2020)
Many developing country governments determine eligibility for anti-poverty programs using censuses of household assets. Does this distort subsequent reporting of, or actual purchases of, those assets? We ran a nationwide experiment in Indonesia where, in randomly selected provinces, the government added questions on flat-screen televisions and cell-phone SIM cards to the targeting census administered to 25 million households. In a separate survey six months later, households in treated provinces report fewer televisions, though the effect dissipates thereafter. We find no change in actual television sales, or reported or actual SIM card ownership, suggesting that consumption distortions are likely small.
Keywords: 330